Functional Geometric Morphometric Analysis of Masticatory System Ontogeny in Papionin Primates. Issue 1 (January 2015) - Singleton, Michelle; Terhune, Claire; Cooke, Siobhán B.; Laitman, Jeffrey T.
ABSTRACT The three‐dimensional configuration of the primate masticatory system is constrained by the need to maximize bite forces while avoiding distraction of the temporomandibular joint (TMJ). Within these bounds, shape variation has predictable effects on functional capacities such as mechanical advantage and gape. In this study, geometric morphometric analysis is used to investigate the ontogeny of masticatory function in papionin monkeys and test the hypothesis that biomechanical constraints determine the location of molar eruption. This "constrained eruption hypothesis" predicts that the distalmost molar (DMX) will occupy a consistent location anterior to the TMJ and that jaw adductor muscles will maintain consistent positions relative to both DMX and TMJ. Craniometric landmarks were digitized on cross‐sectional ontogenetic series of nine papionin species. Form‐space PCA of Procrustes residuals, visualization of Bookstein shape coordinates, and nonparametric ANOVA were used to identify ontogenetic shape trends and test for significant ontogenetic changes in relative landmark positions. In most taxa, DMX maintains a consistent position relative to the TMJ while the anterior dentition migrates anteriorly. Where significant intraspecific ontogenetic differences occur, they involve anterior migration of DMX in later dental stages, likely due to late adolescent growth of the posterior palate. Attachments of the anterior temporalis and deep masseter also maintain consistent positions relative to the TMJ; however, the superficial masseter migrates anteriorly throughout ontogeny. All muscle attachments migrate laterally relative to the TMJ, reflecting positive scaling of adductor PCSA. Overall, results support the constrained eruption hypothesis and suggest mechanisms by which functional capacity is maintained during ontogeny. Anat Rec, 298:48–63, 2015. © 2014 Wiley Periodicals, Inc.